Natural extracts versus sodium ascorbate to extend the shelf life of meat-based ready-to-eat meals. (October 2013) - Price, Alejandra; Díaz, Pedro; Bañón, Sancho; Garrido, Maria Dolores
The effect of grape seed and green tea extracts was compared with effect of sodium ascorbate on bacterial spoilage, lipid stability and sensory quality in cooked pork meatballs during refrigerated storage. Meatballs were stored at 4 ℃ in aerobic packaging for 0, 4, 8, 12 and 16 days under retail display conditions. Lipid oxidation was evaluated as thiobarbituric acid reactive substances, volatile compounds and cholesterol oxidation products. Colour stability was assessed through CIELab parameters. Microbiological spoilage was determined through total viable, mould and yeast and coliform counts. The samples containing green tea and grape seed extracts showed lower levels of thiobarbituric acid reacting substances, major volatile compounds and microbiological counts than the samples with sodium ascorbate. Formation of cholesterol oxidation products was also inhibited to a greater extent. Colour of meatballs and pork meatballs was not affected by refrigerated storage; however, the addition of extracts provided brown shades. The addition of antioxidants did not modify the sensory attributes except for the colour. Green tea and grape seed extracts were more effective than sodium ascorbate at preventing lipid oxidation.